Soluble total antigen derived from Toxoplasma gondii RH strain prevents apoptosis, but induces anti-apoptosis in human monocyte cell line - Rahimi, Hanieh Mohammad; Nemati, Sara; Alavifard, Helia; Baghaei, Kaveh; Mirjalali, Hamed; Zali, Mohammad Reza (Folia parasitologica, 2021)
Apoptosis plays crucial role in the pathogenesis of toxoplasmosis, as it limits further development of the disease. The current study aimed to investigate the effects of different concentrations of soluble total antigen (STAg) of Toxoplasma gondii (Nicolle et Manceaux, 1908) on the apoptotic and anti-apoptotic pathways. PMA-activated THP-1 cell line was sensed by T. gondii STAg and the expression patterns of caspase-3, -7, -8, -9, Bax, Bcl-2, and Mcl-1 genes were evaluated. The results showed statistically significant concentration-dependent overexpression of both Bcl-2 (P-value < 0.0001) and Mcl-1 (P-value = 0.0147). The cas-7 showed overexpression in all concentrations (P-value < 0.0001). The cas-3 was suppressed in concentrations 100, 80, and 40 µg, but statistically significant downregulated in concentrations 10 and 20 µg. The Bax was suppressed in concentrations 100 to 20 µg, while it slightly downregulated 1.42 fold (P-value = 0.0029) in concentration 10 µg. The expression of cas-8 and -9 was suppressed in all concentrations. Our results indicated that T. gondii STAg downregulated and suppressed apoptotic and upregulated anti-apoptotic pathways. The upregulation of cas-7 in this study may indicate the role of T. gondii STAg in activation of inflammatory responses.
Keywords: apoptóza; buněčné linie; Monocytes; Toxoplasmosis; Mcl-1; monocyty; Humans; Cell Line; Toxoplasma; toxoplazmóza; lidé; Soluble total antigen; Toxoplasma gondii; Bcl-2.; Apoptosis